(untitled) (Third Sector Social Economic Review, 2021)
The objective of this article is to question and examine different aspects of qualitative method in social sciences in relation to the case study method. Discussions about the qualitative method in knowledge production is still ongoing. In the International Relations (IR) discipline of social sciences, researches on different theories reveal different approaches to the qualitative method. In the disipline of IR, the method of the case research has become an integral part of qualitative method. Change and substantial progress have resulted in a better and efficient research approach that corresponds to individual researchers’ perspectives. As an important dimension of the qualitative method, case study research on theoretical debates is constantly evolving and becoming more useful. The benefits of the case study method in data collection and knowledge production are observed more. In the case study, it can be possible to diagnose, confirm or falsify different hypotheses. It is possible to test hypotheses better by both tracing out the process and comparing similar or different processes. This may better facilitate theoretical generalizations towards theoritical studies. This work seeks to make contribution to the evaluation of the case study methodology including comparative method and process tracing. This article thus discussed how to develop a better case study method in IR. While the weak and strong sides of the case study method were reviewed, the advantages and disadvantages of a research were examined, evaluated and concluded. A neorealist hypothese about the multipolar system is reviewed to illustrate how case study method, including process tracing and comparison can contribute to theoretical studies and exploration of hypotheses. In the review of Kenneth Waltz’s hypothesis of multipolarity, evaluations about the Crimean War of 1853-56 and the Ottoman-Russo War of 1877-78 were included.